(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Green Marketing is a new concept which has developed a particular importance in the modern market. It is the marketing of products that are presumed to be safe for the consumer and environment. Green Marketing is wide concept which includes a broad range of activities such as consumer products, industrial products and also services. For example resorts in all around the world are promoting themselves as “ecoturist”. Green Marketing Mix consists of 4P’s like marketing, but they are little differing from marketing. In this paper researcher explains why firms are adopting green marketing. This paper discusses the importance of green marketing and also explains the problems, which a firm has to face in adopting green marketing concept. The researcher explains that firms are treating it as moral responsibilities to save the environment and also concludes that it is the customer who demands the product. The responsibility to save the environment is not on the marketer itself, it is also the responsibility of the consumer to dispose the waste in eco-friendly manner. There is great need to aware the consumer about eco-friendly products.